Report on the potential impacts of property tax abatement on rental housing construction in Boston - Patricia Alejandro; Mary Ellen Carter; Denise DiPasquale; Edward L. Glaeser; Adam M. Guren; Paul Willen (Federal Reserve Bank of Boston, 2024)
Boston's high housing costs reflect a historic failure to build enough units to satisfy demand. Interest rates and construction costs have risen recently, and the flow of new market-rate residential housing projects has slowed. To spur more construction, the City of Boston is considering various policy options. Our committee was asked by Boston Mayor Michelle Wu to assess the market impacts of one of these options: real estate tax abatements. This report presents our analysis of the likely effects on the number of units constructed and the costs to taxpayers of various tax abatement alternatives. We do not recommend which policy, if any, the city should pursue; Boston officials are better positioned to assess whether the benefits of these policies warrant the costs to taxpayers.
Keywords: H2; H71; R31; 330; Tax abatement; housing supply; Boston